2011
DOI: 10.1177/0093650210377896
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Variation in Contemporaneous Responses to Hurt in Premarital Romantic Relationships: A Relational Turbulence Model Perspective

Abstract: The authors use the relational turbulence model to derive hypotheses linking characteristics of relationships and reactions to hypothetical hurtful messages from a romantic relationship partner. It was hypothesized that relational uncertainty and perceptions of goal interference and facilitation from a partner predict perceptions of relational turbulence, which in turn predicts the intensity of hurt feelings, negative emotions, and the perceived intentionality of hurt evoked by hypothetical scenarios involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 50 publications
3
85
0
1
Order By: Relevance
“…Two previous studies have applied the relational turbulence model (RTM; Solomon & Knobloch, ) to understand the association between relationship qualities and experiences of hurt within romantic relationships (McLaren, Solomon, & Priem, ; Theiss, Knobloch, Checton, & Magsamen‐Conrad, ). RTM specifies that relational uncertainty and partner interference render people more reactive to relationship events (e.g., Solomon & Knobloch, ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies have applied the relational turbulence model (RTM; Solomon & Knobloch, ) to understand the association between relationship qualities and experiences of hurt within romantic relationships (McLaren, Solomon, & Priem, ; Theiss, Knobloch, Checton, & Magsamen‐Conrad, ). RTM specifies that relational uncertainty and partner interference render people more reactive to relationship events (e.g., Solomon & Knobloch, ).…”
mentioning
confidence: 99%
“…Theiss et al () assessed people's experience of hurt over 6 weeks and found that relational uncertainty and partner interference were positively associated with intensity of hurt, perceived intentionality, and relational damage. McLaren et al () assessed people's contemporaneous responses to hypothetical scenarios depicting a romantic partner being hurtful and found that relational uncertainty and interference from a partner were positively associated with relational turbulence, whereas facilitation from a partner was associated with less turbulence. Furthermore, that study found that relational turbulence was positively associated with intensity of hurt, negative emotions, and perceptions of intentionality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of scholarship has relied on undergraduate student samples to examine hurtful communication, including studies investigating hurt from mothers (Kennedy-Lightsey & Dillow, 2011), in families (Vangelisti et al, 2007), in pre-marital romantic relationships (McLaren, Solomon, & Priem, 2011). Research exploring honest but hurtful messages (Zhang & Stafford, 2008), willingness to confront hurt feelings (Miller & Roloff, 2007), and the biological stress reactions to hurtful messages (Priem, McLaren, & Solomon, 2010) has utilized college-based samples.…”
Section: Discussionmentioning
confidence: 99%
“…The theory defines relational turbulence as a global attribute of relationships, on par with other constructs such as intimacy, satisfaction, and commitment. Items measuring relational turbulence ask people to rate their relationship via adjectives such as chaotic, tumultuous, and stressful (e.g., Knobloch, ; McLaren, Solomon, & Priem, ).…”
Section: Relational Turbulence Theorymentioning
confidence: 99%